Comparing the Relevance of the USE Questionnaire and Heatmap Analysis in Evaluating Usability and User Experience: A Case Study of the Unjani Information Systems Study Program Community Website - Utami, Meisya Putri; Basri, Hasan; Renaldi, Faiza; Destiani, Dea (CV. Publikasi Indonesia, 2025)
Usability and user experience are crucial aspects in designing and evaluating digital systems, as both directly affect user satisfaction, efficiency, and engagement. However, there often exists a gap between users' perceptions of the system’s usability and their actual behavior when using it. This research explores the potential of such gaps by analyzing user perceptions (measured through the USE questionnaire) and actual behavior data (collected from Microsoft Clarity heatmaps). A quantitative approach and visual observation involving 115 questionnaire respondents and 333 recorded user interaction sessions through Microsoft Clarity are employed. The study results indicate a general alignment between users’ positive views and behavioral engagement, such as high usability scores correlating with active duration on the Berita page. However, discrepancies were also identified on the Diskusi pages, where high satisfaction scores did not align with user behaviors like Quick Backs and Dead Clicks, indicating barriers in usability. These findings underscore the importance of integrating subjective and objective data: the USE questionnaire captures views on ease of use, satisfaction, and benefits, while heatmaps reveal behavioral barriers that may be hidden. In conclusion, both approaches complement each other, and when used together, they produce a more comprehensive and implementable user experience evaluation.